TELEVISI LOKAL SEBAGAI MEDIUM PENCITRAAN LOKALIAS DAERAH - Sugihartono, Ranang Agung (Institut Seni Indoensia Surakarta, 2009)
Local television as a imaginary media in a localities exist as a phenomena in order to expressed reality. This article will examine a what kind of contribution need a specific perspective regarding to local identity entirely. According to the main contribution of local television, this article attempt to local materials appearance as well as social educative impacts gained from their program itself. At least the local materials supposed to be news program competence, program production’s competence, local imaginary competence, and Actualization of local competence. Through this article what I would like to strives can not be separated from relationship among existence of media television and imaginary of local product. Based on a mainstream of indigenous localityand imaginary approaches, so that local television has a specific contribution upon social educative’s roles in their own phenomena.Keyword : media television, locality, imaginary approach, social educative.